Non-destructive Analysis of Pamelo Citrus Fruit Maturity with Impedance Spectroscopy Method - Rosiana, Elfirza; Baskara, Hedy Aditya; Setiawan, Jan; Ardianto, Donie Agus; Abdurahman, Abdurahman; Maulana, Riski; Yanti, Fitri (LPPM Universitas Andalas, 2024)
Citrus fruit is a fruit that is favored by the public. The quality of the fruit from the garden to the consumer goes through a long process. Generally, the quality of the fruit is evaluated by a visual judgment ratio that can be wrong. This method also only evaluates the external quality of the fruit. The internal quality of the fruit such as sugar content is determined by a refractometer which belongs to the destructive method, and is not suitable for online quality measurement. A non-destructive and objective method to evaluate the quality of citrus fruits is needed. Electrical Impedance Spectroscopy (EIS) method can be used in non-destructive investigation. In this study, a non-destructive measurement of pamelo orange fruit was developed. The impedance change of pamelo citrus fruits during ripening was observed over a period of one week. The impedance of pamelo orange fruit was measured by AD5933 evaluation board and then the measurement data was analyzed by EIS Spectrum Analyzer software. Frequency-related electrical characteristics were observed, the results showed that the electrical impedance decreased and the phase increased